Risk of Ischemic Bowel Disease in Patients With Atrial Fibrillation Receiving Warfarin or Non-vitamin K Antagonist Oral Anticoagulants - Liao, Jo-Nan; Chan, Yi-Hsin; Kuo, Ling; Tsai, Chuan-Tsai; Lim, Su-Shen; Chao, Tze-Fan (Frontiers in Cardiovascular Medicine, 2022)
Background: Although atrial fibrillation (AF) is a risk factor of ischemic bowel disease, data regarding the incidence of ischemic bowel disease in anticoagulated AF patients were limited. Methods: The present study used the Taiwan National Health Insurance Research Database and included newly diagnosed AF patients aged >20 years without ischemic bowel disease from 2012 to 2018. A total of 69,549 patients taking warfarin or non-vitamin K antagonist oral anticoagulants (NOACs) constituted the final study group. We aimed to study the incidence of ischemic bowel disease in patients with AF receiving warfarin or NOACs. Secondary end points were also analyzed, including ischemic stroke, systemic embolism, myocardial infarction, mortality, intracranial hemorrhage (ICH), major bleeding, and composite adverse events (ischemic bowel disease or ICH or major bleeding). Results: There were 43,787 patients taking NOACs and 25,762 patients taking warfarin. The overall incidence rate of ischemic bowel disease was 0.036% per year and increased with the CHA2DS2-VASc scores (0.013% for patients with a CHA2DS2-VASc score of 0 [males] or 1 [females], 0.022% for those with a CHA2DS2-VASc score of 1 [males] or 2 [females], and 0.039% for those with a CHA2DS2-VASc score ≥2 [males] or ≥3 [females]). The risk of ischemic bowel disease was similar between NOAC and warfarin groups (0.036%/year versus 0.037%/year; adjusted hazard ratio 0.802, P = 0.430), whereas NOAC group had significantly lower risk of secondary end points compared to warfarin group. Conclusions: We reported the incidence of ischemic bowel disease in anticoagulated AF patients from nationwide cohort database and observed a positive correlation between the increase of CHA2DS2-VASc scores and the incidence. Moreover, NOAC was as effective as warfarin for the risk of ischemic bowel disease.